2014
DOI: 10.1371/journal.pcbi.1003807
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Dorsal Gradient across Species Reveals Interaction between Embryo Morphology and Toll Signaling Pathway during Evolution

Abstract: Morphogenetic gradients are essential to allocate cell fates in embryos of varying sizes within and across closely related species. We previously showed that the maternal NF-κB/Dorsal (Dl) gradient has acquired different shapes in Drosophila species, which result in unequally scaled germ layers along the dorso-ventral axis and the repositioning of the neuroectodermal borders. Here we combined experimentation and mathematical modeling to investigate which factors might have contributed to the fast evolutionary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 43 publications
3
35
0
Order By: Relevance
“…This model also proved extremely powerful when comparing nDl gradient formation in related drosophilids. (Ambrosi et al, 2014). In this publication, Ambrosi also suggest that Cactus is the most important element that allows the correct gradient accommodation in embryos of greatly divergent sizes.…”
Section: Two Routes For Dorsal Nuclear Translocation As An Extension mentioning
confidence: 84%
“…This model also proved extremely powerful when comparing nDl gradient formation in related drosophilids. (Ambrosi et al, 2014). In this publication, Ambrosi also suggest that Cactus is the most important element that allows the correct gradient accommodation in embryos of greatly divergent sizes.…”
Section: Two Routes For Dorsal Nuclear Translocation As An Extension mentioning
confidence: 84%
“…In addition to reduced diffusivity resulting in a hallmark shuttling phenotypes, it was also shown that embryos from heterozygous dl null mothers exhibited the hallmark phenotypes to varying degrees (Fig. 2C) [6,17,32]. However, no previous model of the Dl gradient, including our initial models, could reproduce this phenotype when lowering only the dosage of Dl [17,[32][33][34].…”
Section: Evidence Of Shuttling In the Dorsal Gradientmentioning
confidence: 85%
“…Any system with these four features, balanced in the proper way, may exhibit shuttling. Indeed, previous models of the Dl/Cact system, which captured these four features, exhibited shuttling without the express intention of the modelers [32].…”
Section: Evidence Of Shuttling In the Dorsal Gradientmentioning
confidence: 99%
“…Hence, interplay between Toll signaling and the embryo morphology may regulate scaling of the Dorsal gradient function (Ambrosi et al . ). On the dorsal side of the embryo, Dpp (a member of the BMP family) also forms a robust concentration gradient that scales to embryo size (Eldar et al .…”
Section: Scaling Of Gene Expression Boundaries In the Early Drosophilmentioning
confidence: 97%
“…Cross-species analysis of Dorsal activity identified that the threshold response to Dorsal concentration remained relatively stable, but (downstream) Toll activation was highly variable (Chahda et al 2013). Hence, interplay between Toll signaling and the embryo morphology may regulate scaling of the Dorsal gradient function (Ambrosi et al 2014). On the dorsal side of the embryo, Dpp (a member of the BMP family) also forms a robust concentration gradient that scales to embryo size (Eldar et al 2002;Mizutani et al 2005).…”
Section: Scaling Of Gene Expression Boundaries Along the Dorsal-ventrmentioning
confidence: 99%